"How can we measure if our actions are increasing gender equality?”: Insights from a scoping review into gender-responsive monitoring approaches for agrifood stakeholders - Mora, Catalina; Morgan, Miranda; Elias, Marlène (2023)
A recent rapid scoping review identified a lack of clear and accessible guidance to support agrifood stakeholders in measuring their contributions to women’s empowerment and gender equality. In response, we have developed resources to support more effective gender-responsive monitoring, including a curated shortlist of turnkey resources and the Gender Equality in Agrifood Systems: Indicator List (GEASIL).